Odpowiedzi

2010-02-06T18:34:07+01:00

A) (5x²-3x+2)-(2x²-5x+3)=5x²-3x+2-2x²+5x-3=3x²+2x-1
B)(5x²-3x+2)+(2x²-5x+3)=5x²-3x+2+2x²-5x+3=7x²-8x+5
C)(5x²-3x+2)-(4x²+2x-6)=5x²-3x+2-4x²-2x+6=x²-5x+8
D)(5x²-3x +2)+(4x²+2x-6)=5x²-3x +2+4x²-2x-6=9x²-5x-4

1)2x-(x+4)=2x-x-4=x-4
2)1-(t+p)-(t-2)=1-t-p-t+2=-2t-p+3
3)(3x-t+1)-(x+y)+(y-x)=3x-t+1-x-y+y-x=x-t+1
4)(2ab+a+3)-(3ab-a+3)=2ab+a+3-3ab+a-3=-ab+2a
2010-02-06T18:37:18+01:00
A) (5x²-3x+2)-(2x²-5x+3) = 5x²-3x+2-2x²+5x-3 = 3x²+2x-1
B) (5x²-3x+2)+(2x²-5x+3) = 5x²-3x+2+2x²-5x+3 = 7x²-8x+5
C) (5x²-3x+2)-(4x²+2x-6) = 5x²-3x+2-4x²-2x+6 = x²-5x+8
D) (5x²-3x +2)+(4x²+2x6) = 5x²-3x+2+4x²+2x-6 = 9x²-x-4

1) 2x-(x+4) = 2x-x-4 = x-4
2) 1-(t+p)-(t-2) = 1-t+p-t+2 = 3-2t+p
3) (3x-t+1)-(x+y)+(y-x) = 3x-t+1-x-y+y-x = x-t+1
4) (2ab+a+3)-(3ab-a+3) = 2ab+a+3-3ab+a-3 = -ab+2a
2010-02-06T18:39:20+01:00
A) (5x²-3x+2)-(2x²-5x+3)=5x²-3x+2-2x²+5x-3=3x²+2x-1
B)(5x²-3x+2)+(2x²-5x+3)=5x²-3x+2+2x²-5x+3=7x²-8x+5
C)5x²-3x+2)-(4x²+2x-6)=5x²-3x+2-4x²-2x+6=x²-5x+8
D)5x²-3x +2)+(4x²+2x+6)=5x²-3x +2+4x²+2x+6=9x²-x+8

1)2x-(x+4)=2x-x-4=x-4
2)1-(t+p)-(t-2)=1-t-p-t+2=3-2t-p
3)(3x-t+1)-(x+y)+(y-x)=3x-t+1-x-y+y-x=x-t+1
4)2ab+a+3)-(3ab-a+3)=2ab+a+3-3ab+a-3=-ab+2a